PERAN ROH KUDUS DALAM PELAYANAN HAMBA TUHAN BERDASARKAN 1 TESALONIKA 1:4-10 TERHADAP PERTUMBUHAN IMAN JEMAAT - Waruwu, Erlina; Ernamawati Zai, Vesni; Ratnawati (Jurnal Teologi RAI, 2025)
This article discusses the role of the Holy Spirit in the ministry of God's servants based on 1 Thessalonians 1:4–10 and its impact on the growth of the congregation's faith. Genuine ministry cannot be separated from the presence and work of the Holy Spirit, as the Spirit provides power, conviction, and exemplary character in service. The purpose of this study is to analyze in depth how the role of the Holy Spirit is manifested in the ministry of God’s servants and its effect on the quality of the congregation’s spiritual growth. The method used is qualitative with a descriptive-analytical approach, focusing on literature review and conceptual analysis based on relevant theological and practical sources. The analysis shows that the Holy Spirit plays a central role in equipping and guiding ministers, so that the ministry becomes not only informative but also transformative. When ministry is carried out in dependence on the Holy Spirit, the congregation experiences true spiritual growth through life transformation, faithfulness in following Christ, and perseverance in hope. In conclusion, the role of the Holy Spirit in ministry is essential for the growth of the congregation’s faith. The contemporary church must emphasize the active involvement of the Holy Spirit in every aspect of ministry in order to produce spiritually mature believers who grow in faith and become more like Christ.